Microbiological, physical and chemical properties of joruk (fermented fish product) with different levels of salt concentration - Dyah Koesoemawardani; LULU ULYA AFIFAH; NOVITA HERDIANA; A.S. SUHARYONO; ESA GHANIM FADHALLAH; MAHRUS ALI (Society for Indonesian Biodiversity, 2021)
Abstract. Koesoemawardani D. Afifah LU, Herdiana N, Suharyo AS, Fadhallah EG, Ali M. 2021. Microbiological, physical, and chemical properties of joruk (fermented fish product) with different levels of salt concentration. Biodiversitas 22: 132-136. Joruk is a fermented fish product originated in Ogan Komering Ulu Timur, South Sumatra, Indonesia. The aim of this study was to determine the effect of salt on the microbiological, physical and chemical properties of joruk. This research was arranged in a Randomized Complete Block Design (RCBD), with treatment of salt concentrations at 5%, 10%, 15%, 20%, 25%, and 30% (w/w). The follow-up test used the Least Significance Difference (LSD) at 5%. The result of this study showed that the addition of 10% salt produced the best joruk with the best microbiological and chemical properties as follows: total LAB of 8.75 log cfu/g, total microbes of 13.25 log cfu/g, and total mold of 4.27 log cfu/g, pH of 5.85, total lactic acid of 2.97%, Total Volatile Base (TVB) of 153.05 mgN /100g, and water content of 59.33%. Based on this study, it is concluded that the addition of salt at different concentrations significantly affects the pH, total lactic acid, total lactic acid bacteria (LAB), and water content of joruk.